Module for teaching Chicness folk music for dance course at Lin Nan Normal University, Guang Dong, China - ไห่ ช่าง (Academic Journal of North Bangkok University, 2020)
This is an experimental research aimed 1) to study an efficiency of Module for teaching Chinese folk music for dance course at Lin Nan Normal University, Guang Dong, China with the criteria of efficiency (E1/E2) 80/80, 2) to study the satisfaction of first year students learning with Module for teaching Chinese folk music for dance course with the hypothesis of very satisfied. The target group was 30 first year students in semester 2, academic year 2018. The research uses Module for teaching Chinese folk music constructed by the researcher and final satisfaction questionnaire. The information are analyzed by using the simple statistic included percentage, mean, and Standard Deviation. The results were: 1) Module for teaching Chinese folk music for dance course at Lin Nan Normal University, Guang Dong, China has the efficiency 93.25/91.10 which is higher than provided criteria. 2) satisfaction of teaching method found that the students were satisfied at the highest level ( = 4.79, S.D. = 1.37).